We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website.
Please click on "Accept cookies" if you agree to the setting of cookies. Cookies that do not require consent remain unaffected by this, see
cookie policy and privacy policy.
DECLINE COOKIES

#2

#3**+1 **

Ehh I guess. I'm thinking it would be this for the max. height: -120/2(-16) which equals 3.75 so it would be [0,3.75] and then I got the rest :P i'll show my work if anyone wants me to.

RainbowPanda
Aug 21, 2018

#4**+2 **

h(t) = -16t^2 + 120t + 6

The time to reach the max height = -120 /[ 2 * -16 ] = -120 / -32 = 3.75 sec

And....to find the max height, plug this value back into the function =

-16(3.75)^2 + 120 (3.75) + 6 = 231 ft

Note that the change in height is [231 - 6 ] = 225 ft

So...the average rate of change in height from intial height to max height = [231- 6] / 3.75 =

225 / 3.75 = 60 ft / sec

CPhill Aug 21, 2018

#6**+2 **

Well....two great minds couldn't possibly be incorrect, could they ???

LOL!!!

CPhill
Aug 21, 2018

#7**+1 **

Well my mind isn't very great haha, but you're never incorrect, so this must be the correct answer. ^-^

RainbowPanda
Aug 21, 2018